Gamma-aminobutyric acid treatment promotes resistance against Sogatella furcifera in rice - Jan, Rahmatullah; Asif, Saleem; Asaf, Sajjad; Lubna; Khan, Zakirullah; Khan, Waleed; Kim, Kyung-Min (Frontiers in Plant Science, 2024)
The Sogatella furcifera (Horváth) (Homoptera: Delphacidae) is a white-backed planthopper ( WBPH) that causes "hopper burn" in rice, resulting in severe yield loss. Gamma-aminobutyric acid (GABA) is a well-known neurotransmitter that inhibits neurotransmission in insects by binding to specific receptors. In this study, we investigated the potential role of GABA in modulating rice resistance to WBPH and evaluated possible defense mechanisms. The experiment was conducted in green house in pots consist of four groups: control, GABA-treated, WBPH-infested, and WBPH-infested treated with GABA. Among the various tested OPR) and melatonin biosynthesis-related genes (TDC, T5H, ASMT, and SNAT). Our study suggested that GABA increases resistance against WBPH infestation by regulating antioxidant defense system, TCA cycle regulation, phytohormonal signaling, and PR gene regulation.